Induced Pluripotent HD Monkey Stem Cells Derived Neural Cells for Drug Discovery. (July 2017) - Kunkanjanawan, Tanut; Carter, Richard; Ahn, Kwan-Sung; Yang, Jinjing; Parnpai, Rangsun; Chan, Anthony W. S.
Huntington's disease (HD) is a neurodegenerative disease caused by an expansion of CAG trinucleotide repeat (polyglutamine [polyQ]) in the huntingtin ( HTT ) gene, which leads to the formation of mutant HTT (mHTT) protein aggregates. In the nervous system, an accumulation of mHTT protein results in glutamate-mediated excitotoxicity, proteosome instability, and apoptosis. Although HD pathogenesis has been extensively studied, effective treatment of HD has yet to be developed. Therapeutic discovery research in HD has been reported using yeast, cells derived from transgenic animal models and HD patients, and induced pluripotent stem cells from patients. A transgenic nonhuman primate model of HD (HD monkey) shows neuropathological, behavioral, and molecular changes similar to an HD patient. In addition, neural progenitor cells (NPCs) derived from HD monkeys can be maintained in culture and differentiated to neural cells with distinct HD cellular phenotypes including the formation of mHTT aggregates, intranuclear inclusions, and increased susceptibility to oxidative stress. Here, we evaluated the potential application of HD monkey NPCs and neural cells as an in vitro model for HD drug discovery research.